The effect of playing surface on injury rate: A review of the current literature - Dragoo, J. L.; Braun, H. J. (Sports Medicine, 2010)
Synthetic playing surfaces are widely used for field and court sports. Artificial turf surfaces are commonly used as an alternative to natural grass, while outdoor surfaces like clay and acrylic are also prevalent. The effect of these synthetic surfaces on injury rates has not been clearly established. The available literature is largely limited to football and soccer data and the majority of studies are short-term. Confounding variables such as climate, player position and footwear, as well as varying definitions of injury, also make it difficult to draw firm conclusions about the general effect of artificial playing surfaces on injury rates. Many peer-reviewed studies cite a higher overall rate of injury on first- and second-generation artificial turf surfaces compared with natural grass. Despite differences in injury type, the rate of injury on third-generation and natural grass surfaces appears to be comparable. It also appears that clay is significantly safer than either grass or hard court tennis surfaces, but this is a conclusion drawn with limited data. Further research investigating overall injury trends as well as sport-specific data is needed to draw more definitive conclusions regarding the effect of artificial playing surfaces on injury rates.